The value of nature in the Andean worldview for environmental education - Lucero Geraldine , Aguilar López (2024)
The knowledge crisis associated with the anthropocentric and destructive Western worldview has led to an environmental crisis. In response, the Andean worldview is being reevaluated for its way of understanding the world, which regards Nature as a living and sacred entity. This perspective fosters a close, sensitive, and respectful relationship between humans and "Mother Earth." This vision is reflected in the daily practices of Andean communities, where invaluable learning spaces spontaneously emerge; these should transcend their origins and be incorporated into schools and community settings. Thus, the values of the Andean worldview can have a profound impact on contemporary environmental education. This essay highlights the concept of nature in the Andean world and how this approach contributes to environmental education in our current context.